Związki wolności ekonomicznej i rozwoju społeczno-gospodarczego w Unii Europejskiej w latach 2007-2013 - Hajder, Krzysztof (Rocznik Integracji Europejskiej, 2015)
This paper analyses the counter-crisis policy by means of examining crucial measures of socio-economic development, such as GDP per capita, sovereign debt, budget deficit, the share of public income and expenditure in GDP, unemployment rate, the percentage of people at risk of poverty, etc. The analysis concerns EU member states in 2007–2014 and concentrates on the division of states in terms of economic freedom which facilitates the assessment of economic efficiency in terms of the involvement of state in economy.